The Interplay of English as a Foreign Language Learners’ Interest, Self-Efficacy, and Involvement - Liu, Zhengyuan (Frontiers in Psychology, 2022)
Learners’ involvement has been a critical issue since the origin of teaching and learning; it is developed quickly in previous decades. The enhancement of motivational aspects like self-efficacy appears to have high impacts on learners' success and the other concept is interest, an extensively investigated concept in various subjects, which has hardly been scrutinized regarding language learning. This review intended to scrutinize the association among students' self-efficacy, their academic interest, and students’ involvement. It is significant to pinpoint that the current review can help educational administrations, professional improvement centers, and policymakers to consider the above-mentioned issues in the progression of language education to develop their involvement.